The Impacts of Brexit on the Economic and Political Security of Northern Ireland - Puguh Toko Arisanto; Ilham Aditya Pamungkas (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
This research examines the effects of Brexit in 2016 on the economic and political security of Northern Ireland. The primary objective of this study is to identify how a policy of a certain group of countries can have a significant impact on other countries such as Northern Ireland. To analyse this issue, the research employs the concept of national security, with a specific focus on economic and political security. A descriptive qualitative method is employed to collect data through a review of relevant literature. Authors find that Brexit brought about Northern Ireland's economic and political security which has led to a disrupted supply of goods, a rise in prices, a decline in people's welfare, and a clash between Unionists and Nationalists, resulting in the overthrow of the Northern Ireland Prime Minister.